2022
DOI: 10.1186/s12870-022-03854-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptome and network-based analysis of yellow leaf mutant Ginkgo biloba

Abstract: Background Golden leaf in autumn is a prominent feature of deciduous tree species like Ginkgo biloba L., a landscape tree widely cultivated worldwide. However, little was known about the molecular mechanisms of leaf yellowing, especially its dynamic regulatory network. Here, we performed a suite of comparative physiological and dynamic transcriptional analyses on the golden-leaf cultivar and the wild type (WT) ginkgo to investigate the underlying mechanisms of leaf yellowing across different se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…The differentially expressed TFs identified in our study belonged to gene families such as bHLHs, NACs, MYB-related, ERFs, B3s, C2H2s, GRASs, LBDs, MYBs, WRKYs, and GLKs. Similar findings were reported in a yellow-leaf mutant of G. biloba [28]. The suppression of bHLH71-like in pepper plants led to elevated levels of zeaxanthin and antheraxanthin, implying a role for bHLH71-like as a promoter of Car biosynthesis in the yl1 yellow pepper mutant [90].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The differentially expressed TFs identified in our study belonged to gene families such as bHLHs, NACs, MYB-related, ERFs, B3s, C2H2s, GRASs, LBDs, MYBs, WRKYs, and GLKs. Similar findings were reported in a yellow-leaf mutant of G. biloba [28]. The suppression of bHLH71-like in pepper plants led to elevated levels of zeaxanthin and antheraxanthin, implying a role for bHLH71-like as a promoter of Car biosynthesis in the yl1 yellow pepper mutant [90].…”
Section: Discussionsupporting
confidence: 82%
“…× 'Whoa Nellie' unveiled alterations in chloroplast ultrastructure and reduced gene expression linked to Chl biosynthesis and photosynthesis, leading to Chl deficiency in the mutant leaves [24]. Similarly, transcriptomic analysis and weighted gene co-expression network analysis (WGCNA) profiling in Ginkgo biloba identified differentially expressed genes (DEGs) involved in pigment metabolism and putative transcription factors (TFs) associated with its leaf coloration [28]. Through an integrated transcriptomic and metabolomic investigation in Cucumis melo, enzyme genes and metabolites predominantly associated with central carbon metabolism, photosynthesis, flavonoid metabolism, and energy metabolism were identified [29].…”
Section: Introductionmentioning
confidence: 99%
“…A similar increased expression of CLH2 was also found to be related to the reduced chlorophyll contents in a leaf-color mutant of Cymbidium sinense [24]. In the yellow-leaf bud mutant cultivar 'Wannianjin' of Ginkgo biloba, dynamic transcriptome analyses suggested that both the decreased expression of the biosynthesis gene, i.e., HEMA, and the increased expression of the degradation gene (CLH) caused a low chlorophylls accumulation [25]. Meanwhile, a previous study indicated that the upregulated expression of the CLH and NYC1 genes in the yellow-green leaf WY16-13 of wucai (Brassica campestris) germplasm might have accelerated the degradation of the chlorophylls, resulting in the yellowing of the plant's leaves [26].…”
Section: The Underlying Mechanism Of the Chlorina Phenotype In Hymentioning
confidence: 63%
“…In the downstream process of carotenoid metabolism, a list of enzymes can cleave carotenoid to produce phytohormone abscisic acid (ABA) and strigolactones, and the downregulated expression of these downstream genes had been extensively demonstrated to be involved in the catabolism of carotenoid ( Nisar et al., 2015 ; Yuan et al., 2015 ). The expression of NCED gene in ginkgo was increased in yellow leaves in autumn, while decreased in green leaves in summer ( Sun et al., 2022 ). Previous studies in zucchini reported that NCED and CCD genes were downregulated in yellow and orange peels, which was agreement with the accumulation of yellow lutein ( Obrero et al., 2013 ; Niu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%